Editorial Board and Guideline for the Authors - Mimbar Pendidikan, Editor Journal (Universitas Pendidikan Indonesia, 2016)
MIMBAR PENDIDIKAN journal will provide a peer-reviewed forum for the publication of thought-leadership articles, discussion, applied research, case and comparative studies, and expert comment and analysis on the key issues surrounding the educational studies and its various aspects. Analysis will be practical and rigorous in nature.